Reduce VAT on Food to Zero - Lukas Scholle (Wirtschaftsdienst)
Abstract The economic consequences of the war in Ukraine are taking a toll on goods prices in Germany and elsewhere. Prices on energy inputs to production, heating and mobility have risen sharply as well as food prices. As a possible policy response to these rising prices, the reduction of the VAT to zero on basic food is being discussed. In the debate many counter-arguments like the pass-through rate, the distributional effects and the financing have come up. In this paper, I argue that these points of critique hardly stand up to closer scrutiny. Both theoretical and practical arguments suggest that reducing the VAT to zero is an appropriate measure to mitigate inflation and provide relief.